Harihara depicted as a synthesis of Shiva and Vishnu - Temples of India Project Team (Jio Institute, 2024)
Harihara is depicted as a synthesis of Shiva and Vishnu. In this form, Shiva occupies the right half, adorned with a jatamukuta (crown of matted hair), while Vishnu occupies the left half, crowned with a kiritamukuta (a cylindrical crown associated with Vaishnava iconography). In his upper right hand, Harihara wields a trishula (trident), symbolizing Shiva’s power, while his lower left arm holds a shankha (conch), symbolizing Vishnu’s presence. Nandi, Shiva’s mount, is carved at the bottom right, and a kalasha (pitcher) adorned with vegetal motifs is depicted at the bottom left, symbolizing abundance.